2007
DOI: 10.1007/s12020-007-9021-2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulation of growth hormone receptor gene expression: involvement of both the PI-3 kinase and MEK/ERK signaling pathways

Abstract: The mechanism(s) of insulin's effects on growth hormone receptor (GHR) gene expression are poorly understood. Using rat hepatoma cells, we have previously shown that insulin treatment reduces GHR mRNA and protein in a time- and concentration-dependent manner, at least in part via down-regulation of GHR transcription. The present study determines whether the phosphatidylinositol-3 kinase (PI-3 kinase) and mitogen activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) pathways are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…In rat hepatoma cells, low dose insulin administration results in GH-induced stimulation of JAK2 phosphorylation however high dose insulin treatment results in inhibitory effect [69,86]. The effect of insulin on GHR function appears to be mediated by the PI-3 kinase and MAPK/ERK pathways [69,87,88]. It has been shown that insulin increases GH signalling by enhancing GHinduced activation of MAPK/ERK pathway through post signalling cross-talk [88].…”
Section: Insulin Effect On Gh Receptor Signallingmentioning
confidence: 99%
“…In rat hepatoma cells, low dose insulin administration results in GH-induced stimulation of JAK2 phosphorylation however high dose insulin treatment results in inhibitory effect [69,86]. The effect of insulin on GHR function appears to be mediated by the PI-3 kinase and MAPK/ERK pathways [69,87,88]. It has been shown that insulin increases GH signalling by enhancing GHinduced activation of MAPK/ERK pathway through post signalling cross-talk [88].…”
Section: Insulin Effect On Gh Receptor Signallingmentioning
confidence: 99%
“…Numerous epidemiologic studies have reported that metformin is associated with decreased risk of cancer incidence [2–7]. Metformin is supposed to inhibit cellular growth and proliferation by lowering insulin levels through the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/ mammalian target of rapamycin (mTOR) pathway pathways [8, 9]. Recent published study has also shown that metformin exhibits an anti-apoptotic effect on podocytes under high glucose conditions through activation of adenosine monophosphate-activated protein kinase (AMPK) and inhibition of mTOR signaling [10].…”
Section: Introductionmentioning
confidence: 99%
“…The GHS-R1a is expressed throughout the brain including in feeding and metabolism-associated areas like the arcuate nucleus (ARC) [18,19,20], as well as regions important in memory (Cornu Ammonis (CA)2, CA3, dentate gyrus of the hippocampus) and reward (ventral tegmental area, substantia nigra pars compacta (SNpc), dorsal raphe) [19,21,22]. The GHS-R1a is a g-protein coupled seven transmembrane receptor.…”
Section: Introductionmentioning
confidence: 99%